The Study Skills Handbook - Cottrell, Stella (2013)
This title introduces higher-level study skills and allows students to develop a deeper understanding of the learning process itself, encouraging a reflective and well-informed approach to study.
Previous edition: 2008.
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: Study skills; Education